(untitled) (Journal of Social Sciences Review, 2025)
The present study was designed to investigate the impact of love of money on emotional labour and hedonic behaviour among live video call streamers. Data was online collected from (N=100) Pakistani Muslim live video call streamers. The sample was consisted of adolescence, early adults and middle adults. All streamers participated in study were at least 3 month experienced in live video streaming. Love of Money Urdu Scale (Tang & Chiu, 2003), Emotional Labour Urdu Scale (Yang et al., 2019), and Hedonic Behaviour Urdu Scale (Babin et al., 1994), were administered to measure constructs of the study. Correlational survey research method was used in the present investigation. Results showed significant negative correlation of love of money with emotional labour and hedonic behaviour among live video streamers. t-test revealed that male streamers scored high on love of money, while female streamers scored high on emotional labour and hedonic behaviour. ANOVA revealed that adolescents do more emotional labour and hedonic behaviour than early adults and middle adults. Limitations, suggestions and practical implications are also added in the study to pave road for future research.